Analysis of Influencing Factors of Urban Road Traffic Accidents Based on Association Rules - Yang, Jiaqi (Transactions on Computer Science and Intelligent Systems Research, 2024)
Urban road traffic conditions are complex and changeable. Affected by multiple factors, the mechanism and main influencing factors of traffic accidents are difficult to define. This paper aims to study the distribution characteristics and main factors influencing urban road traffic accidents. According to the collected data of urban traffic accidents in Britain, the basic characteristics including trunk road flap, weather conditions, time, maximum speed limit, first road classification and other factors are all analyzed, with association rules used to explore its influence mechanism. From aspects of vehicle, environment and road, this paper not only focuses on the influence mechanism of the interaction of two factors and three factors in urban road traffic accidents, but also puts forward targeted accident prevention measures accordingly.